Neural activity during processing Chinese irony text: An event-related potential study - Shi, Hanwen; Li, Yutong (Frontiers in Neuroscience, 2022)
Objective：Irony is an indirect language with unpredictability. Understanding irony is more difficult than understanding literal language, consuming more cognitive resources. The objective of this study is to explore processing differences between irony and literal sentences with event-related potential (ERP) technology. Method: This study manipulated sentence types as: predictable literal sentences, unpredictable literal sentences, and irony. Participants were asked to read three different types of sentences and their neural responses were recorded. Results: Compared with predictable literal sentences, unpredictable literal sentences and irony elicited larger amplitude of N400 components, while no significant difference between the latter two. In addition, the amplitude of P600 showed no significant difference induced by the three type sentences. Conclusion: The semantic retrieval of irony and unpredictable literal sentences have difficulties in the early stage of processing, and both possess similar the processing pattern, but in the late stage, it is similar to that of predictable literal sentences.